Educational signification extracted from the verses of mother in the holy Quran and their applications in the family - Al-Nefaie, Nourah Dakhel (Journal of Educational and Psychological Sciences, 2025)
The aim of this study was to deduce educational signification from the verses of mother in the holy Quran and their applications in the family. The researcher used the descriptive approach with its deductive approach. researcher concluded a set of findings, the most prominent of which are: the verses included the devotional contents, and it amounted to (5) contents, the most prominent of which were: benevolence, thanking God for his blessings, patience for affliction, honoring parents, and relying on God. the verses included moral contents and amounted to (5) contents, namely: Honesty, courage, justice, mercy and Chastity. The study made some recommendations one of the most important of them was: activating the educational contents derived from the verses of the Holy Quran, especially what came from them in the verses of the mother in the educational field in general and in the family in particular.